Microwave synthesis of nanoparticulate EuFeO3 and its visible light photocatalytic activity. Issue 181 (13th June 2017) - Tang, Peisong; Chen, Haifeng; Lv, Chunyan; Wang, Kunyan; Wang, Yongya
ABSTRACT: Using Eu(NO3 )3 ·6H2 O and Fe(NO3 )3 ·9H2 O as raw material, the nanoparticulate EuFeO3 was directly synthesized by a one-step microwave route without additional high temperature calcination process. The prepared sample was characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetry and differential thermal analysis (TG-DTA), Fourier transform infrared spectroscopy (FT-IR) and UV-visible diffuse reflectance spectroscopy (DRS). The results show that the EuFeO3 is single phase perovskite, and its morphology is nanoparticle with an average diameter of about 60–80 nm. The prepared nanoparticle has an optical band gap of 2.3 eV, and exhibits strong visible-light absorption. The photocatalytic activity of nanoparticulate EuFeO3 was investigated in experimental simulation wastewater containing 10 mg/L methyl orange (MO). The photocatalytic experiment indicates that the prepared nanoparticulate EuFeO3 was highly visible-light activities for the degradation of MO. It is suggested that the narrow band gap and the strong visible-light absorption are responsible for the high visible-light photocatalytic activity of the prepared EuFeO3 .